Expertise and representation in financial institutions: UK legislation on pension fund governance and US regulation of the mutual fund industry - Clark, G (Routledge, 2007)
Decision making is often the responsibility of committees, boards and agencies assuming that many issues are best resolved by smaller, specialised units of decision making. The product of 'representative democracy' and a pragmatic response to 'large numbers' and 'complexity', these bodies are thought to efficaciously combine representation with expertise. Governments use these types of institutions in a variety of ways, and have become a key institution of New Labour's 'third way'. However, there is a growing tension between representation and expertise. If the former provides legitimacy for the latter, the latter may be compromised by the former in matters of requiring sophisticated judgement relative to market agents. It is argued that the tension between representation and expertise is growing for two reasons: perceived 'shortfalls' in democratic practice have prompted governments to broaden the representativeness of many public and private institutions set against an apparent need for greater levels of sophistication in decision making driven by financial markets. These arguments are developed through discussion of that which was inherited from 19th century liberalism, a set of analytical distinctions between deference and delegation, and two examples drawn from the UK and US finance industries. In conclusion, it is noted that apparent solutions, such as relying wholly upon experts, are fraught with danger: there may be such a disconnection between expertise and moral commitment that the former without the latter may give decisions that are hard to justify on any ground.